Evidence-based Practice of School Management in PAUD Darussalam Pudak Payung Central Java Indonesia - Taulany, Himmah; Kumaira Herdiantoputri, Safira; Intan Rochmawati, Nur; Fauziah, Syifa; Cahyanti, Dian (KnE Social Sciences, 2022)
This study aims to analyze the management of the Darussalam Pudak Payung Early Childhood Education Center, Central Java, Indonesia. The type of research used is descriptive qualitative research. The data collection techniques used are observation, interview, and documentation techniques. The key informant is the Principal, and their claims are compared with the claims of other informants, namely teachers, parents, and children. The data analysis technique used was the Miles and Huberman interactive analysis models, namely Data Reduction, Data presentation, and Conclusion Drawing or Verification. The results showed that the management of the Darussalam Pudak Payung Early Childhood Education Center implemented eight standards. Of the eight standards, five standards have been achieved or have advantages, namely Child Development Achievement Level Standards, Content Standards, Process Standards, Management Standards, and Assessment Standards. The implementation of the eight standards was not entirely successful. Of the eight standards, 3 standards have not been achieved or have shortcomings, namely the Standards for Educators and Education Personnel, Standards for Facilities and Infrastructure, and Standards for Financing. Keywords: Management School, Early Childhood Education Standards, Early Childhood Education